(untitled) (Gestión y Gerencia, 2019)
The positivist and postpositivist conception of science constitute philosophical streams that support the construction of contemporary managerial thinking. This article makes a theoretical approach to reflect about contemporary managerial thinking, as an interpretative construction of the social sciences, based on the contributions of Pooper, Kuhn and Lakatos; for this, knowledge in the social sciences, contemporary management as a social science, and the construction of managerial knowledge are analyzed; then the positivist and postpositivist conception of science exposed by these philosophers is described, in order to establish analogies between their contributions and contemporary managerial thinking. It is concluded that contemporary management is considered until now, from a perspective that accommodates the instrumental, measurable and verifiable, which must be overcome to lead to the perspective of considering it as a construction and reconstruction of stories, and personal and social experiences, so they show a new direction in the way of conceiving knowledge in the management field and from the axiological perspective, this goes beyond instrumental and strictly economic rationality, to aim to individual and collective human development, allowing the achievement of a management that answers the challenges of post-modern society